A silver staining method for single-cell gel assay - Nadin, Silvina Beatriz (2001)
The single-cell gel assay (comet assay) is a very useful microelectrophoretic technique for evaluation of DNA damage and repair in individual cells. Usually, the comets are visualized and evaluated with fluorescent DNA stains. This staining requires specific equipment (e.g., a high-quality fluorescence microscope), the slides must be analyzed immediately, and they cannot be stored for long periods of time. Here we describe, using human lymphocytes, some modifications of the silver staining for comets that significantly increase the sensitivity/reproducibility of the assay. This silver staining was compared with fluorescence staining and commercial silver stains.